Challenges in therapy of severe COVID-19 pneumonia with giant pneumatocele in a preterm newborn: how to optimize mechanical ventilation? - Rsovac, Snežana; Čobeljić, Mina; Vukašinović, Nadja; Milošević, Katarina (Vojnosanitetski pregled, 2024)
Introduction. Coronavirus disease 2019 (COVID-19) pneumonia is a potentially life-threatening condition that can require the use of mechanical ventilation (MV) and is rare in the neonatal population. Giant pneumatocele is an extremely rare complication of MV, which is practically unknown in neonates. Case report. We report a case of a two-week-old premature infant who developed severe acute respiratory distress syndrome (ARDS) due to COVID-19 and pneumatocele as a complication of MV. The newborn was admitted in a life-threatening condition with persistent hypercapnia, which, therefore, required prolonged MV. Chest computed tomography (CT) was done to assess the degree of fibrosis caused by COVID-19, and as an accidental finding, a pneumatocele was observed. The patient was immediately started on high-frequency oscillatory ventilation as a way of conservative treatment. After prolonged duration and gradual separation from MV, the patient was extubated, and oxygen therapy was gradually discontinued. The patient was discharged in good condition, and the follow-up chest CT showed complete regression of pneumatocele. Conclusion. Optimization of MV parameters and adequate treatment of complications such as ARDS or giant pneumatocele in neonates is an area that still requires further research, primarily due to the specificity of the neonatal age compared to adult patients.